Peranan Pr Digital Kominfo Kabupaten Tanah Datar Dalam Publikasi Kegiatan Melalui Media Sosial: indonesia - ria edlina (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2022)
Public Relations aims to create, maintain and develop good relationships, form understanding, bridge the relationship between agencies/institutions and the public, both internally and externally. PR as a communicator from agencies/institutions must be able to be trusted by the public because PR is the first person who will deal directly with the public. Then PR as a supporter in the management function has a strategic role because it can strengthen the reputation of the agency/institution in the public eye. In the development of communication technology there is a development in the PR profession, namely what is called digital PR. Digital PR is not much different from conventional PR, which is a strategic communication process that aims to build mutually beneficial relationships between an organization and its publics. But what makes the difference is the medium of communication. While conventional PR works on events and publications in conventional media, digital PR uses more online/website technology-based media. Relations with the media are one of the functions of digital PR. Current technological developments make it easy for everyone to convey and receive news, therefore PR with its media relations function must be able to predict everything that happens in the public. Therefore, digital PR is required to be able to work with technological developments, one of which is to become digital public relations for agencies/institutions. The public will certainly find it easier to know every activity carried out by their agencies/institutions with the help of information provided by PR through publications, both from press releases, news, events and using new media as a means of disseminating online information provided to the public.